Modeling views for the semantic web: As a mechanism for modeling sub-ontologies - Chang, Elizabeth; Dillon, Tharam S.; Rajugan, R.; Feng, L. (IEEE, 2005)
The emergence of Semantic Web (SW) and related technologies promise to make the web a meaningful experience. Web services (WS) enable distributed access and discovery of internal, Enterprise functions and services over the web, in a secure controlled environment. Yet, high level modeling, design and querying techniques proves to be a challenging task for organizations that are hoping to utilize the SW paradigm for their industrial and WS applications. Conversely both, SW and WS paradigm can benefit, if some of the traditional database concepts, functionalities and models are made adoptable to the new SW/WS paradigm. To address one such issue, in this paper, we propose a view model for Semantic Web that can be utilized in the new web information system framework, the SW/WS. First we outline our view model and then briefly provide discussion on its properties and some modeling issues with the help of an industrial case study example.